Development of a multiplex fluorescent microsphere immunoassay for diagnosis of the porcine disease complex - Ransburgh, Russell (Kansas State University, 2015)
The Porcine Disease Complex (PDC) results in major economic problems for swine producers. PDC outbreaks result in increased mortality, decreased feed efficiency, higher cull rates, prolonged days to market and increased treatment costs. This disease involves the interaction and participation of many multifactorial etiologies including both bacterial and viral organisms playing a role in disease initiation and progression. The most common viral pathogens associated with the PDC include porcine reproductive and respiratory syndrome virus (PRRSV), porcine circovirus (PCV2) and swine influenza virus (swIV). The recent outbreak of porcine epidemic diarrhea virus (PEDV) in the US swine herd has made the PDC even more complicated. In aid of the prevention and control of the PDC, veterinarians and producers require fast and efficient diagnostic tests for controlling the disease. In this study, we have generated recombinant nucleocapsid antigens to these viruses for use in a Luminex™ technology-based fluorescent microsphere immunoassay (FMIA). Utilizing these recombinant nucleocapsid antigens, the FMIA was developed to simultaneously detect antibodies in serum from animals infected with PEDV, PRRSV, SwIV and PCV2. The FMIA was developed based on testing experimentally derived standard positive and negative control sera, and the diagnostic specificity and sensitivity were compared to that generated from the classical enzyme-linked immunosorbent assay (ELISA) or hemagglutination inhibition (HI) test. Based on an evaluation of 4147 serum samples with known serostatus, the multiplex FMIAs reached greater than 97.5% sensitivity and 92.3 % specificity. Results showed that multiplexing did not affect the diagnostic sensitivity or specificity of each individual assay. This work provides a platform for the development of multiplex assays for detecting various swine pathogens simultaneously and aids in preventing and controlling the PDC.
Keywords: Multiplex; Fluorescent microsphere immunoassay; Porcine disease complex; Luminex; Veterinary Medicine (0778); Virology (0720)